Konsep Nasab, Istilhâq, dan Hak Perdata Anak Luar Nikah - Muhammad Taufiki (AHKAM : Jurnal Ilmu Syariah, 2012)
Abstract: The Concept of Family, istilhâq, and civil rights of children born out of wedlock. One of the basic rights that all newborns have is the right to family. This means that the moment a child is born it immediately gets the right to belong to his parents’ family, in addition to other rights that relate to being related to that family. However, not all children are born with as good a lot as that. If that is the case, Islam has several ways for that child to get to have family. A family can be sought through iqrâr (declaration), evidence, and istilhâq. Once that family has been linked, civil rights, which he gets from having that father, automatically apply to that child. Children born out of wedlock can be linked to a family with people who are willing to be compassionate towards the child’s mother, when that birth doesn’t happen as a result of adultery. In that case, it is permissible if the nature of the birth is either uncertain or didn’t happen through adultery. A child born to a married couple considered unlawful can be linked to another family and with them get his or her civil rights as needed from the father of that family.Keyword: family, istilhâq, civil right, children born ouy of wedlockAbstrak: Konsep Nasab, Istilhâq, dan Hak Perdata Anak Luar Nikah. Anak yang terlahir ke dunia memiliki hak nasab sebagai salah satu hak dasar yang dimilikinya. Ini berarti bahwa saat anak terlahir langsung mendapatkan hak nasab dari ayahnya dengan hak-hak lain yang melekat akibat adanya kaitan nasab itu. Akan tetapi, tidak semua anak terlahir dengan nasib sebaik itu. Dalam hal ini, Islam memiliki beberapa cara untuk mendapatkan nasab itu. Nasab bisa didapat melalui iqrâr (pengakuan), pembuktian, dan istilhâq. Bila nasab itu sudah terkait, maka hak-hak perdata anak secara otomatis melekat pada anak itu yang dapat diperolehnya dari ayahnya. Anak luar nikah bisa dikaitkan nasabnya dengan orang yang menanam benihnya ke rahim ibu si anak, bila hal itu terjadi bukan karena zina. Dalam hal ini, bisa karena syubhât atau hal lain selain zina. Anak yang terlahir dalam pernikahan yang dinggap tidak sah bisa dikaitkan nasabnya dengan ayahnya dan mendapatkan hak perdata sebagaimana mestinya, bila hal itu dilakukan oleh ayahnya.Kata Kunci: nasab, istilhâq, hak perdata, anak luar nikahDOI: 10.15408/ajis.v12i1.966